Analisis Kesalahan Penggunaan Huruf Kapital dan Tanda Baca Siswa Kelas 2 SDN Karawaci 1 Kota Tangerang - Aqwal, Syifa Masyhuril; Nurfadhillah, Septy; Nuraeni, Yeni (Lembaga Yasin AlSys, 2022)
This study aims to describe and describe errors in the use of capital letters and punctuation for grade 2 students at SDN Karawaci 1 Tangerang City. This study uses descriptive qualitative methods, namely methods that involve researchers directly to observe the object being studied. The results of this study were found in 26 students in the answers to the simple sentence writing questions that had been analyzed, there was the highest capital letter writing error in the month name indicator as many as 16 students or 61.5%. Meanwhile, the highest indicator punctuation error is at the dot at the end of the sentence as many as 7 students or 26.9%. This shows that the majority of grade 2 students at SDN Karawaci 1 understand punctuation, but there are still many who do not understand the use of capital letters.